Impact of a School Mental Health Program on Children's and Adolescents' Socio-Emotional Skills and Psychosocial Difficulties - Aurora Adina Colomeischi; Diana Sinziana Duca; Liliana Bujor; Petruta Paraschiva Rusu; Ilaria Grazzani; Valeria Cavioni (MDPI AG, 2022)
The challenges of today's society demand high levels of socio-emotional skills in children and adolescents; therefore, mental health is an important issue to be addressed and promoted in schools. The present study aims to investigate the effectiveness of a school mental health program (Promoting Mental Health at Schools; PROMEHS) designed to promote socio-emotional learning and prevent psychosocial difficulties in children and adolescents. The study was conducted on a sample of 1392 students (evaluated by 104 teachers) from kindergarten (n = 446), primary school (n = 426), secondary school (n = 354), and high school (n = 166). A quasi-experimental study design with experimental and waitlist control groups was used to evaluate the program's effectiveness. Students were non-randomly assigned to the experimental (n = 895) and control group (n = 497). Students belonging to the experimental group received one-hour lessons once a week for 12 weeks. The teachers evaluated their students' social-emotional skills, strengths, and difficulties before and after the intervention. The results indicated the effectiveness of the PROMEHS program in improving social-emotional skills for all school levels, reducing internalizing problems in primary and secondary school chil-dren, and reducing externalizing issues for kindergarten and primary school children. The PROMEHS program is a promising approach to enhancing childrens' and adolescents' social and emotional skills and to decreasing psychosocial difficulties, such as internalizing and externalizing problems.